Analisis Perilaku Masyarakat dalam Pengelolaan Sampah di Kota Padang Panjang - Wartin, Angeli; Syarief, Azhari (Lembaga Yasin AlSys, 2025)
Waste is one form of waste found in the environment. Its source, form, type and composition are strongly influenced by the level of community culture and natural conditions. This study aims to determine community behavior and factors that influence community behavior in waste management in Padang Panjang City. This study used descriptive methods with quantitative and qualitative approaches, primary data collection techniques were carried out by questionnaire. The population in this study were people in Padang Panjang City, 100 respondents were selected to be research informants. The results showed that the community had “Very Good” waste management behavior. Factors that influence behavior, 1) Public knowledge about waste management is “High”. The general behavior of the community in waste management, namely by managing waste at home such as making unique, interesting crafts, and making eco enzyme, disposing of waste to the nearest TPS and burning waste. 2) Waste management facilities and infrastructure are categorized as “High” in 6 urban villages, while the other 10 are “Medium”. Facilities and infrastructure owned or provided by the community and government in Padang Panjang City are in the form of waste collection containers made of wood, cemented TPS, iron to attach garbage, drums or trash cans. 3) Government policy in Mayor Regulation No. 29/2018 encourages community involvement in waste management through education and information. Counseling activities in Padang Panjang City are attended by the community. Several communities and waste bank managers were awarded certificates for their involvement as inspirational figures in waste management.